HOUT-11. EXTENSIVE BRAINSTEM INFILTRATION, NOT MASS EFFECT, IS A COMMON FEATURE OF END-STAGE CEREBRAL GLIOBLASTOMAS. (11th November 2019) - Drumm, Michael; Dixit, Karan; Grimm, Sean; Kumthekar, Priya; Lukas, Rimas; Raizer, Jeffrey; Kam, Kwok-Ling; McCord, Matthew; Sachdev, Sean; Kruser, Timothy; Steffens, Alicia; Javier, Rodrigo; et al.
Abstract: BACKGROUND: Progress in extending the survival of glioblastoma (GBM) patients has been slow, suggesting that preclinical and clinical trial approaches may not fully take into account the nature of this cancer. A better understanding of why GBM patient survival remains poor is critical to developing new strategies. Postmortem studies on GBM can shed light on how GBM spreads and how GBM patients are dying. METHODS: The brains of 25 GBM patients were autopsied and examined for gross and microscopic abnormalities. Clinical-pathologic correlations were accomplished through detailed chart reviews. Data were compared with older published autopsy GBM studies that predated the use of concurrent radiation and temozolomide (RT/TMZ). RESULTS: In pre-RT/TMZ GBM autopsy series, mass effect was observed in 72% of brains, with herniation in 50% of cases. Extensive infiltration of tumor into the brainstem occurred in only 21% of those older cases. In the current series, only 7 of 25 (28%) GBMs showed mass effect (P=0.0004), and none (0%) showed herniation (P< 0.0001). However, extensive GBM infiltration through the cerebral peduncles, into the brainstem, was present in 17 cases (68%, P< 0.0001), with accompanying destruction of the brainstem and white matter tracts. There was a direct correlation between longer patient survival and the presence of brainstem infiltration (P=0.001). CONCLUSIONS: With improving care, severe mass effect is less common in GBM patients today, whereas life-threatening brainstem invasion is now more frequent. This has major implications regarding preclinical GBM models, as well as the design of clinical trials aimed at further improving patient survival.